Pengambilan Keputusan Dengan Basis Data: Studi Literatur Peluang Manajemen Pada Teknologi Informasi - Emilda Nada (Institute of Information Technology and Social Science (IITSS), 2021)
Decision making is one of the important functions in management. A database is a set of structured data that can be used to support decision making. Information technology (IT) has provided new opportunities for management in leveraging databases for decision-making. This literature study aims to assess management opportunities on information technology in decision making with databases. The study was conducted by collecting data from a variety of literature sources, such as books, journals, and scientific articles. The results of the study show that IT has provided various opportunities for management in decision-making with databases. These opportunities include: Improved data quality. IT can help improve data quality by providing tools and techniques to collect, store, and manage data more efficiently and effectively. Development of decision-making models and techniques. IT can help develop more sophisticated and accurate decision-making models and techniques. Improved data accessibility. IT can help improve the accessibility of data for decision makers. The study concludes that IT has become an important tool for management in decision-making with databases. IT can help management to make more informed, faster, and more efficient decisions. Keywords: Decision Making, Database, Information technology, Management, Opportunities